2019
DOI: 10.1553/moegg159s190
|View full text |Cite
|
Sign up to set email alerts
|

Brücke und/oder Sprungbrett: Sopron/Ödenburg, die Rolle der ungarischen Grenzstadt im Rahmen der Binnenmigration nach 1989

Abstract: It is the main aim of this study to analyse the role of a Hungarian medium-sized town located by the Austrian border, Sopron/Ödenburg, in internal migration. The change of the political system after 1989 has had its impact not only on the social and economic development of the town, but also on perception of the town's geographical location. Located in the western periphery of the country, near to the Iron Curtain during the decades of Socialism, Sopron/Ödenburg found itself in a much more favourable position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…He generally attempted to make a positive impression on the interviewer by explaining how he has sought to help workers but that they often leave regardless because they lack the competence to remain at a workplace. The migratory bird metaphor represents worker fluctuation and the practice of using Hungarian firms as springboards to obtain higher‐paying jobs in Austria (Kiss et al, 2020). Seasonal job opportunities in Austrian agriculture, particularly in viticulture, lead to seasonal fluctuation in Hungarian factories, further strengthening the “migratory species” analogy: People return to manufacturing firms in winter and ask to return, as employees and intermediaries both reported ( Intermediary 1 and 3, Employer 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…He generally attempted to make a positive impression on the interviewer by explaining how he has sought to help workers but that they often leave regardless because they lack the competence to remain at a workplace. The migratory bird metaphor represents worker fluctuation and the practice of using Hungarian firms as springboards to obtain higher‐paying jobs in Austria (Kiss et al, 2020). Seasonal job opportunities in Austrian agriculture, particularly in viticulture, lead to seasonal fluctuation in Hungarian factories, further strengthening the “migratory species” analogy: People return to manufacturing firms in winter and ask to return, as employees and intermediaries both reported ( Intermediary 1 and 3, Employer 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, geography and related social sciences literature have only sparsely conceptualized the interrelation of dehumanization and labour migration throughout the labour process (Mezzadri, 2019). Following Winders and Smith (2019), we integrate the analysis of capitalist A 2017 questionnaire survey found that 15% of newcomers to Sopron who arrived after 2009 found employment in low-skilled jobs (Kiss et al, 2020). This share might be even higher because the survey underrepresented people living in worker hostels and other low-cost accommodations.…”
Section: Dehumanization and Migrant Labourmentioning
confidence: 99%
See 3 more Smart Citations